New strategies to optimize renal haemodynamics. Issue 6 (December 2020) - Suarez, Jonathan; Busse, Laurence W.
Abstract : Purpose of review: This review discusses the macrocirculatory and microcirculatory aspects of renal perfusion, as well as novel methods by which to measure renal blood flow. Finally, therapeutic options are briefly discussed, including renal-specific microcirculatory effects. Recent findings: The optimal mean arterial pressure (MAP) needed for preservation of renal function has been debated but is most likely a MAP of 60–80 mmHg. In addition, attention should be paid to renal outflow pressure, typically central venous pressure. Heterogeneity in microcirculation can exist and may be mitigated through appropriate use of vasopressors with unique microcirculatory effects. Excessive catecholamines have been shown to be harmful and should be avoided. Both angiotensin II and vasopressin may improve glomerular flow through a number of mechanisms. Macrocirculatory and microcirculatory blood flow can be measured through a number of bedside ultrasound modalities, sublingual microscopy and urinary oxygen measurement, Summary: Acute kidney injury (AKI) is a common manifestation of organ failure in shock, and avoidance of hemodynamic instability can mitigate this risk. Measurement of renal haemodynamics is not routinely performed but may help to guide therapeutic goals. A thorough understanding of pathophysiology, measurement techniques and therapeutic options may allow for a personalized approach to blood pressure management in patients with septic shock and may ultimately mitigate AKI.